Psicanálise on-line : de que “conexão” se faz necessária para alcançar a subjetividade de nossa época? - Ebert, Keli Virginia (2023)
This study seeks to bring some considerations about the operationality of transference and the handling of payment at an online and free psychoanalytical clinic. In order to make these constructions, narratives of psychoanalysts were used, specifically of the analysts that work as volunteers in a project that has as a specificity the format of online and free consults. And so, the investigation of the clinical practices is one of the main thematic axes of this research and has direct relations to the second axe, specifically, the Freudian and Lacanian theoretical framework that substantiates and withholds theorically the operationality of transference and payment in this specific type of clinical work. It is an investigation that will produce theoricalpractic constructions about fundamental concepts to the psychoanalytical clinic, seeking to bring the necessary connection to reach the subjectivity of our time, a temporality that is marked by subjects bathed in digital culture and molded by the logic of capital. Thus, this research seeks to develop theorical-practic constructs about the operationality of transference and payment at a free-online dispositive, without it deforming the conceptual theory of these clinical fundaments. The results were constituted throughout the narrative extracts articulates to the psychoanalytical theory. It was through the Freudian legacy about the public clinics that this research contextualized the question of gratuity in the investigated field. Although, if ever since Freud we find theorical contributions about payment in psychoanalysis, the same cannot be said about online clinics for we do not have theorization in Freud or Lacan about a type pf clinic that did not exist, which convenes us to articulate the studied practices to the existing theory in order to extract theorical-practical constructs about what is transference and payment in the type of clinic that was researched. To the fulfilment of this study, the psychoanalyst researcher directed her hearing to the experiences narrated by the psychoanalysts through Focal Group meetings. These narratives were then articulated to the psychoanalytical theory, thus forming the conceptual clinical reports of this Search. And so, we have a work that seeks to tie possible lashings through the investigated clinical practice and the psychoanalytical theory in order to contribute to the theorical-practical psychoanalytical aspects of this type of clinic.